Radiotherapy for Adrenal Metastasis from Hepatocellular Carcinoma: A Multi-Institutional Retrospective Study (KROG 13-05) - Jung, Jinhong (PLoS One, 2016)
Although the adrenal glands are not common sites of metastasis from hepatocellular carcinoma (HCC), this metastasis can be met in patients with advanced HCC in some clinical settings. However, the effectiveness of radiotherapy against such metastases is unclear. Therefore, we performed the present multi-institutional study to investigate tumor response, overall survival (OS), treatment-related toxicity, and prognostic factors after radiotherapy. We retrospectively reviewed 134 patients who completed a planned radiotherapy for their adrenal metastases. Complete response was noted in 6 (4.3%), partial response in 48 (34.0%), and stable disease in 78 patients (55.3%). The median OS was 12.8 months, and the 1-, 2-, and 5-year OS rates were 53.1%, 23.9%, and 9.3%, respectively. Grade 3 anorexia occurred in 2 patients, grade 3 diarrhea in 1, and grade 3 fatigue in 1. Multivariate analyses revealed that the following factors had significant effects on OS: controlled intrahepatic tumor; controlled extrahepatic metastasis; and Child-Pugh class A. Although patients with adrenal metastasis from HCC had poor OS, radiotherapy provided an objective response rate of 38.3% and disease stability of 93.6%, with minimal adverse events. Therefore, radiotherapy for these patients could represent a good treatment modality, especially for patients with controlled intrahepatic tumors, controlled extrahepatic metastasis, and good hepatic function.